2021
DOI: 10.1007/s10668-021-01962-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the environmental Kuznets curve (EKC) hypothesis: does government effectiveness matter? Evidence from 170 countries

Abstract: The lack of studies that examined the influence of government effectiveness on environmental pollution and whether it formulates the environmental Kuznets curve (EKC) hypothesis motivated this research. Therefore, this research examines the role of government effectiveness on CO 2 emission in 170 countries. To achieve the research aims, the system generalized method of moment model is applied while categorizing the countries into three groups: namely high, moderate, and low government effectiveness countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Second, since the Paris Agreement in 2015 the pressure on national governments has increased to find solutions to environmental damage, while minimizing the negative impact on economic growth and development. As a result, a variety of strategies, such as environmental regulations, information programs, innovation policies, environmental subsidies, and environmental taxes have been implemented, particularly in Europe (Al-Mulali et al, 2021). Consequently, government effectiveness plays an important role in eliminating environmental damage and social injustice both by implementing and safeguarding policies, as well as motivating through direct participation in environmental and social agendas.…”
Section: Government Effectiveness and Corporate Sustainable Performancementioning
confidence: 99%
“…Second, since the Paris Agreement in 2015 the pressure on national governments has increased to find solutions to environmental damage, while minimizing the negative impact on economic growth and development. As a result, a variety of strategies, such as environmental regulations, information programs, innovation policies, environmental subsidies, and environmental taxes have been implemented, particularly in Europe (Al-Mulali et al, 2021). Consequently, government effectiveness plays an important role in eliminating environmental damage and social injustice both by implementing and safeguarding policies, as well as motivating through direct participation in environmental and social agendas.…”
Section: Government Effectiveness and Corporate Sustainable Performancementioning
confidence: 99%
“…Empirical studies have showed that GE can reduce the number of deaths in case of extreme weather even as in the case of tropical cyclones [16]. The possibility of countries to create a relationship between economic growth and green sustainability in the sense of the Environmental Kuznets Curve-EKC [17] depends on GE and especially on the level of human capital of politicians [18]. GE plays an essential role in promoting green economy even in developed and in developing countries [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…References GE, Covid 19 Pandemic and Health Issues [7], [8], [20], [23], [40] GE, Public Debt and Taxation [9], [15], [27], [41] GE, Cultural, Educational and Social Issues [10], [26], [43] GE, Institutions and Legal Order [11], [21], [25], [32], [35], [31], [47] GE, Energy and Environmental Sustainability [12], [16], [18], [19], [30], [24] GE, e-Government, and ITC Sector [13], [14], [24], [22], [34], [36], [37], [39], [46] GE, Economic Growth and Development [22], [28], [33], [44], [45] Methodology and Statistical Analysis [48], [49], [50], [51], [52], [53], [54], [1] Theoretical Frameworks [42], [17], [2], [5],...…”
Section: Literature Review By Main Themes Main Themesmentioning
confidence: 99%
“…Control of corruption improves GE [47]. [7], [8], [20], [23], [40] GE, Public Debt and Taxation [9], [15], [27], [41] GE, Cultural, Educational and Social Issues [10], [26], [43] GE, Institutions and Legal Order [11], [21], [25], [32], [35], [31], [47] GE, Energy and Environmental Sustainability [12], [16], [18], [19], [30], [24] GE, e-Government, and ITC Sector [13], [14], [24], [22], [34], [36], [37], [39], [46] GE, Economic Growth and Development [22], [28], [33], [44], [45] Methodology and Statistical Analysis [48], [49], [50], [51], [52], [53], [54], [1] Theoretical Frameworks …”
Section: Literature Reviewmentioning
confidence: 99%